Quantitative and Qualitative Assessment of Marketed Nutraceuticals for Active Ingredients and Heavy Metals for Safety and Efficacy (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The global nutraceutical market is expanding fast, and people nowadays are inclined towards nutraceutical supplements for daily micronutrient needs and health benefits in some disease conditions. Hence, ensuring the safe and effective use of these supplements is the need of the hour. The current study is aimed at determining the accuracy and regulatory compliance of marketed nutraceutical formulations by quantifying the active nutraceutical ingredients and heavy metal content in these formulations using advanced analytical techniques. Total 12 marketed formulations were selected and analyzed in NABL (National Accreditation Board for Testing and Calibration Laboratories) accredited laboratory using High-performance liquid chromatography (HPLC) and inductively coupled plasma-mass-spectrometry (ICP-MS). The quantified values were compared with label-stated values and recommended values as per FSSAI. The quantified values in two lycopene samples varied significantly (-16 and +16%) from the label stated content and were found non-compliant with the regulatory recommendations. The measured intake values of calcium and vitamin D varied from 24 to 204% from the recommended daily allowances established by FSSAI. The quantified daily intake values varied from 4.2 to 58 mg and from 4 to 21.5 mg for lycopene and lutein, respectively. Heavy metal content determination resulted in two samples deviating from the tolerance limits of heavy metals for lead and arsenic. The mean values for lead and arsenic were found to be 2.482 ± 6.921 and 0.311 ± 0.655 ppm, respectively. The present study results provided vital information on the composition of marketed nutraceutical formulations. The regulatory agencies require stringent monitoring practices to ensure compliance with the existing regulatory guidelines to provide the consumer safe and effective nutraceutical products.